Sosialisasi Dan Edukasi Publik Pasar Modal Di SMA Negeri 1 Dolok Masihul Kabupaten Serdang Bedagai - Gunawan, Didik; Sianipar, Cristin Natalia; Cahyadi, Willy; Hutauruk, Rapat Piter Sony; Rahayu, Rahayu; Suwita, Alya (STIE Bina Karya, 2025)
Currently, many schools do not provide financial knowledge to their students. Students should learn about investment early in accordance with the development of technology and science. Therefore, many students do not understand investment and capital markets, so they do not have the enthusiasm to save for the future. The purpose of this program is to increase students' knowledge about investment in the capital market and reduce the impact of low interest in investing in the capital market. In addition, the purpose of this service is to provide education and training on investment in the capital market to students of SMA Negeri 1 Dolok Masihul, Serdang Bedagai Regency. This activity is expected to motivate students to try to invest in the capital market.